2012
DOI: 10.1002/pen.22130
|View full text |Cite
|
Sign up to set email alerts
|

Capillary flow of low‐density polyethylene

Abstract: The capillary flow of a commercial low-density polyethylene (LDPE) melt was studied both experimentally and numerically. The excess pressure drop due to entry (Bagley correction), the compressibility, the effect of pressure on viscosity, and the possible slip effects on the capillary data analysis have been examined. Using a series of capillary dies having different diameters, D, and length-to-diameter L/D ratios, a full rheological characterization has been carried out, and the experimental data have been fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…When B s l ≈1, we have macroscopically obvious slip. For the present data, we get 0.442 < B s l < 1, showing a strong slip effect in the range of simulations, again unlike the LDPE melt, which shows no slip 39. It should be noted that the other HDPE‐42 used in our recent paper29 has similar slip behavior but a higher slip exponent b = 5.73.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…When B s l ≈1, we have macroscopically obvious slip. For the present data, we get 0.442 < B s l < 1, showing a strong slip effect in the range of simulations, again unlike the LDPE melt, which shows no slip 39. It should be noted that the other HDPE‐42 used in our recent paper29 has similar slip behavior but a higher slip exponent b = 5.73.…”
Section: Methodssupporting
confidence: 60%
“…This is defined as When B p =0, we have no pressure dependence of the viscosity. For the present data, we get 5.3 × 10 −4 < B p < 1.6 × 10 −3 , showing a weak dependence of viscosity on pressure in the range of simulations, unlike the LDPE melt 39. More details are given in Table IV.…”
Section: Methodsmentioning
confidence: 48%
“…These functions are independent of the strain-memory function (hence separability of the functions or factorized K-KBZ model), and only and can be determined from dynamic data of the viscoelastic moduli. As an example we give in Figure 4 and Table 1 the fitting of experimental and data for an LDPE melt [45] and an HDPE melt [46], where it is shown that a spectrum of 8 relaxation times, ranging from 10 −4 s to 10 +3 s, is able to capture well the data at all frequencies. It should be noted that the fitting is not very difficult and can be done even with an MS Excel software, provided that one uses a reasonable number of relaxation times (8 for polymer melts or 3 for polymer solutions) with initial guesses for the relaxation times submultiples or multiples of 10 and appropriate initial guesses for the relaxation moduli [30,47].…”
Section: Data Fittingmentioning
confidence: 99%
“…By comparing the experimental data with the results from finite element analysis software, MoldFlow Part Advisor, they found that the analysis software was not suitable for predicting the filling flow in a 0.5‐mm diameter channel. Ansari et al . studied the capillary flow of a commercial low‐density polyethylene (LDPE) melt both experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%